(3GdQJHI aj WQGFa GdMSjIs - (3YHO GdQMef Hf fUQ Hf YHO Gddg, CHh GdfLjH, LdGd GdOjf GdYOhj GdTjRQj,J (B590 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdUGdM YHO GdQMef CMeO Gddg Ydi eG CfYe hHYO abO SCdfi dfUjH GdMSHI hGdfXQ ai eUGdM GdQYjI Cf CLeY eNJUQkG cGajkG ai Sdhc fgL GdMSHI GdHGH GdChd ajeG jLH Ydi GdeMJSH ef TQhW GdMSHI s
(3BNQgG (B:s
(3jLH Cf jchf GdeMJSH YGdekG aEfg Gf cGf LGgdkG GMJGWJ Ydjg GdCehQ hhbY ai GdeMXhQ Je gPG GdcJGH s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B197s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B- (3GdbGgQI (B((3eYGQa YGeI Mdje (B5) s
Keywords: (3GdSjGSI hGdGLJeGYs